Development of Learning Media “Let’s Go Deutsch!“ Based on Flash with Familie und Beruf Theme for Eleven Grade MAN 1 Kota Malang - Fitria Yunta Rosada (Journal DaFIna - Journal Deutsch als Fremdsprache in Indonesien, 2019)
This research aims to develop learning media “Let’s Go, Deutsch!“ to be used for XI grade students MAN 1 Kota Malang. “Let’s Go, Deutsch!“ is based on flash and focused on vocabulary on Familie und Beruf theme. This media contains vocabulary, expressions, videos, and quizes.The type of research is Research and Development (R&D) that use Hoge, Tondora, and Marelli method. The develoment method that originally has seven steps is modified ti five steps. “Let’s Go, Deutsch!“ has been validated by material expert and media expert. This media has been tested to 29 students of XI Language grade MAN1 Kota Malang. The instruments used in this research are questionnaire forms. The research method is qualitative descriptive.The result of this Research and Development shows that “Let’s Go, Deutsch!“ is worth to be used and can used as intermediary in the delivering the materials. The subjects also stated that this media can motivated them to learn vovabularies with fun way.